Techniques for Absorption into Indonesian and the Acceptance of Loan Words Related to Covid-19: Socioterminology Approach - Lalu Muhamad Helmi; Mahsun Mahsun; Burhanuddin Burhanuddin (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
This study answers two questions: what equivalence rules of terms are dominantly found in the absorption words during the Covid-19 pandemic, and how acceptable these terms are in the Indonesian-speaking community. The data were collected by using documentation or observation method, supported by the use of a questionnaire. The data were analyzed by using intralingual equivalence and descriptive analysis methods. The results show that 33 foreign terms were matched using translation techniques, ten words with absorption techniques, and two words with combined translation and absorption techniques. Furthermore, the acceptability of absorption terms during the Corona virus pandemic is 39%, while 61% indicates the unacceptability of absorption terms during the Corona virus pandemic.